Perbandingan Strategi Marketing Syariah dan Marketing Konvensional dalam Menarik Dana dari Masyarakat - Ahmad Yamany Arsyad; Haris Maupa; Jusni Jusni (JUDICIOUS, 2023)
In terms of attracting of public funds as one of the functions of financial institutions needed the right strategy, if the concept of strategy is not clear, the decision will be subjective and based on intuition and ignore other decisions. The aim of the research was to determine the ratio and advantage of conventional marketing strategy and syariah marketing strategy. The research was a descriptive qualitative study conducted in BPR Prima Sengkang and BMT As’adiyah Sengkang. The data were analyzed using IFE Matrix, EFE Matrix, and SWOT Matrix methods. The results of the research indicate that IFE Matrix and EFE Matrix of BPR Prima has a score of 2.81 and 2.80, while IFE Matrix and EFE Matrix of BMT As’adiyah Sengkang has a score of 3.41 and 3.38. This means that the strategy implemented by BMT As’adiyah Sengkang to attract public funds is more effective than the one implemented by BPR Prima is in quadrant IV, while BMT As’adiyah is in quadrant I. This indicates that syariah marketing strategy implemented by BMT As’adiyah is more superior than conventional marketing strategy implemented by BPR Prima Sengkang.